Does New York City really have as many rats as people?. Issue 4 (October 2014) - Auerbach, Jonathan
<x xml:space="preserve">Abstract</x> Jonathan Auerbach, winner of the YSS/Significance Young Statisticians Writing Competition, uses statistical methods to challenge an urban legend.